Tapak Liman (Elephantopus scaber L.) Leaves Ethanol Extract Improves the Production of IL-6 and IL-17 Cytokines in Mice with Bleomycin-induced Pulmonary Fibrosis - Nabilah, Sarah Nahdah; Christina, Yuyun Ika; Dwijayanti, Dinia Rizqi; Rifa’i, Muhaimin; Djati, Muhammad Sasmito (The Journal of Experimental Life Science, 2024)
IL-6 and IL-17 are pro-inflammatory and pro-fibrotic cytokines that increase pulmonary fibrosis due to lung alveolar epithelial cell damage. Tapak liman leaves (Elephantopus scaber L.) have anti-inflammatory and anti-asthmatic properties. This study aimed to investigate the effects of the Elephantopus scaber L. ethanol extract (ESEE) on IL-6 and IL-17 produced by CD4+ and CD8+ in the bleomycin-induced pulmonary fibrosis mice model. Fifty-six male BALB/c mice will be divided into seven groups consisting of healthy mice (N), vehicle mice (V), pulmonary fibrosis (PF), Dexamethasone (DEX) as a drug control, and three doses of ESEE (0.0504, 0.1008, and 0.2016 mg.kg-1 BW). ESEE will be administered orally, followed by intraperitoneal bleomycin injection for 14 days. Mice are then dissected on days 7 and 14, and the spleen will be isolated for analysis of the expression of IL-6 and IL-17. The results showed that ESEE effectively reduced levels of IL-6 and IL-17 cytokines produced by CD4+ and CD8+ T cells, and doses three of ESEE (0.2016 mg.kg-1 BW)  (0.2016 mg.kg-1 BW) showed the most effective reduction activity than the Dexamethasone group. The treatment was proven to reduce the expression of IL-6 and IL-17 in mice with a model of pulmonary fibrosis. Keywords: bleomycin, Elephantopus scaber L., IL-6, IL-17, pulmonary fibrosis.